2021
DOI: 10.3389/fnagi.2021.766306
|View full text |Cite
|
Sign up to set email alerts
|

Senescence in Primary Rat Astrocytes Induces Loss of the Mitochondrial Membrane Potential and Alters Mitochondrial Dynamics in Cortical Neurons

Abstract: The decline in brain function during aging is one of the most critical health problems nowadays. Although senescent astrocytes have been found in old-age brains and neurodegenerative diseases, their impact on the function of other cerebral cell types is unknown. The aim of this study was to evaluate the effect of senescent astrocytes on the mitochondrial function of a neuron. In order to evaluate neuronal susceptibility to a long and constant senescence-associated secretory phenotype (SASP) exposure, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This deregulated glutamate metabolism in senescent astrocytes is a common feature of NDs (Figure 5) [207]. It was also shown that senescent astrocytes decreased neuronal mitochondrial membrane potential and altered neuronal mitochondria functionality after being cocultured with neurons [175]. The authors suggested that this could be due to the fact that senescent astrocytes either lost their ability to secrete factors required for the proper function of neurons or that they gained neurotoxic effect through the secretion of SASP factors [175].…”
Section: Senescent Astrocytes and Age-related Neurodegenerative Diseasesmentioning
confidence: 96%
See 1 more Smart Citation
“…This deregulated glutamate metabolism in senescent astrocytes is a common feature of NDs (Figure 5) [207]. It was also shown that senescent astrocytes decreased neuronal mitochondrial membrane potential and altered neuronal mitochondria functionality after being cocultured with neurons [175]. The authors suggested that this could be due to the fact that senescent astrocytes either lost their ability to secrete factors required for the proper function of neurons or that they gained neurotoxic effect through the secretion of SASP factors [175].…”
Section: Senescent Astrocytes and Age-related Neurodegenerative Diseasesmentioning
confidence: 96%
“…Due to their proliferative capacity, astrocytes also undergo cellular senescence that Cohen et al, named as "astrosenescence" [174]. Numerous studies show that astrocytes can display senescence after exhausted replication, oxidative stress, proteasome inhibition, high glucose, HIV infection, X radiation, hydrogen peroxide, or in the course of aging [175][176][177]. In contrast to reactive astrogliosis, the cellular senescence of astrocytes is a permanent state [174].…”
Section: Morphological and Molecular Features Of Senescent Astrocytesmentioning
confidence: 99%
“…Therefore, the accumulation of ASP+ and Rh123 in the mitochondria may reduce by a senescence-induced decrease in the mitochondrial membrane potential. 24) Thus, a decrease in the mitochondrial membrane potential may partially affect the results of the uptake assay.…”
Section: Gradual Induction Of Sa-β-gal Staining By Long-termmentioning
confidence: 99%
“…protein expression in terms of fold changequantitative or semi-quantitativebiogenesis[47]rat testes, leidig cellsfluorescence microscopy of MitoTrackerfluorescence intensitysemi-quantitativebiogenesis[48]rat primary cortical astrocytesmicroscopy, biochemical analyses; Western blottingmitochondria mass; OXPHOS, % relative expression of mt. proteinssemi-quantitativenot tested[49]mouse synaptic boutons of axons; neuronsfluorescence microscopy of MitoTracker; immunogold stainingnormalized to cell area, mitochondria length per length of axon; mean fluorescence (normalized to cell area); mitochondrial areasemi-quantitativenot tested[50]mouse diet-induced fatty liver in C57BL/6J/biochemical analyses; Western blottingCS activity; mt protein: tissue protein; TG contentsemi-quantitativenot tested[51]mouse astrocytes cultured cellsfluorescence microscopy of MitoTrackerfluorescence intensitysemi-quantitativenot tested[52]rat Myc null fibroblastsflow cytometry using MitoTracker and NAOfluorescence intensitysemi-quantitativebiogenesis[53]mouse embryonic fibroblastsflow cytometry analysis; fluorescence microscopy of using MitoTrackerfluorescence intensitysemi-quantitativebiogenesis and mitophagy[54]mouse embryonic fibroblastsflow cytometry analysis; fluorescence microscopy of using MitoTrackerfluorescence intensitysemi-quantitativeautophagy[55]rhesus monkey presynaptic boutonselectron micr...…”
Section: Quantitative Aspect Of Heterogeneity Of Mitochondrial Conten...mentioning
confidence: 99%